Mechanical evaluation of timber conservation processes by bending tests - Henriques, M. D. (2013)
This paper presents the laboratory work performed with the purpose of understanding the mechanical performance of 340x20x20 mm maritime pine wood samples degraded by rot fungi when treated with a biocide product followed by consolidation through impregnation with a polymeric product. Four commercially available products were used: a water-based biocide, BC, a solvent-based biocide, X, an acrylic consolidant, PB (PB 72), and an epoxy-based consolidant, E. Seven sets of specimens each one having a varied range of fungal degradation were prepared. Then the product combinations were applied by brush to six sets of specimens (E, X-E, BC-E, PB, X-PB, BC-PB) of which one was left untreated for control, 0-0. Finally all sets were subjected to static bending strength test until rupture. Results showed that the acrylic and epoxy-based products lead to increased mechanical capacity of the consolidated wood up to 100% in some cases in specimens with 70% of MOE loss. The results presented the same order of magnitude for both wood consolidants. The previous application of biocide did not have a significant impact in the behavioral pattern of the consolidant: a marked improvement of the bending strength of the degraded specimens after treatment and consolidation. These results demonstrated the feasibility of combining biocide/consolidation products, and provide indications of interest to the application of this technique to extend the lifespan of wood elements moderately degraded by fungi in old buildings.